CTIM-21. AN AGE-SPECIFIC BIOMARKER IN NEWLY-DIAGNOSED GLIOBLASTOMA PATIENTS TREATED WITH RADIATION, NIVOLUMAB AND BMS-986205. (12th November 2021) - Kim, Miri; Ladomersky, Erik; Zhai, Lijie; Bollu, Lakshmi; Bell, April; Lauing, Kristen; Rabin, Erik; Horbinski, Craig; Lukas, Rimas; Wainwright, Derek
Abstract: INTRODUCTION: We previously determined that advanced age plays a negative role in the survival outcome of human recurrent glioblastoma (GBM) patients treated with immune checkpoint blockade. Here we investigate the immunologic "signature" of younger patients who are < 65 years of age and older adult GBM patients who are ≥ 65 years of age that undergo simultaneous treatment with standard radiation, nivolumab (anti-PD-1 mAb), and BMS-986205 (a potent IDO enzyme inhibitor) and are newly diagnosed with O 6 -methylguanine-DNA methyl-transferase (MGMT) unmethylated GBM. Our objective was to identify age-dependent immunologic changes before and after treatment with immunotherapy. METHODS: Patients ≥ 18 years old with newly diagnosed MGMT unmethylated GBM, KPS ≥ 70, and minimal steroid use were eligible for enrollment in this phase 1 trial. PBMCs and serum were drawn at baseline and routine post-treatment time points followed by mass spec analysis of kynurenine (Kyn) and tryptophan (Trp) metabolites, RNAseq, and 18-color flow cytometric analysis. RESULTS: 8 younger adults with a median age of 50 years old and 4 older adults with a median age of 68.5 years old were studied. The median overall survival of younger and older adults was 368 and 108.5 days, respectively ( p =0.032, HR 4.8 for age). BMS-986205 treatment decreased the Kyn/Trp ratio of all patients irrespective of age. RNAseq analysis found significant age-related changes using Gene Ontology pathway analysis of T cell related immunity, lymphocyte activation, and NK cell mediated immunity. Flow cytometric analysis is ongoing. CONCLUSIONS: Similar to what was reported in older adult mice treated with simultaneous RT, anti-PD-1 mAb, and IDO enzyme inhibitor, advanced age negatively affected the survival in older adult human GBM patients treated with an analogous clinical approach. Future determination of whether the age-related biomarker profile can be used diagnostically and therapeutically is now under investigation.